A COMMUNITY-BASED QUR'ANIC EDUCATION PARK DEVELOPMENT MODEL TO INCREASE PARTICIPATION AND LEARNING QUALITY - Ali, Mahrus; Prabowo, Galuh; Algifari, Muhammad Fikri (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The main objective of the study was to implement a community-based Qur'anic Education Center management model to improve community involvement and the quality of Qur'anic learning. This is based on the argument that the sustainability and effectiveness of non-formal education, such as the Qur'anic Education Park, is highly dependent on the support and active involvement of the surrounding community. This research uses a qualitative method with a case study approach to analyze the management of a community-based Qur'anic Education Park at the Sritanjung Qur'anic Education Park in Rogojampi Banyuwangi. Data were collected through participatory observation, in-depth interviews with managers, community leaders, and santri guardians, and documentation studies. Data analysis was carried out using interactive analysis techniques, including data reduction, data presentation, and conclusion drawing. Data validity was strengthened through triangulation of sources and methods. This study aims to provide a comprehensive picture as well as recommendations for strategies to improve participation and quality of learning in community-based Qur'anic Education Centers. The results of this study indicate that community participation in the management of the Sritanjung Rogojampi Qur'anic Education Park is still passive, focusing more on material support than strategic involvement. This is due to the lack of awareness and socialization of the management of the Al-Qur'an Education Park. In addition, the competence of educators is still an obstacle because the majority teach voluntarily without adequate training, so learning methods are less innovative. The lack of collaboration with external parties such as mosques, NGOs and the government also hinders the development of the Qur'anic Education Park. Therefore, it is necessary to increase community involvement, training for educators, and strengthening cooperation networks to increase the effectiveness and sustainability of religious education for students.